PODCASTER’S AWAL MINGGU COMMUNICATION STRATEGY IN CREATING PODCAST CONTENT ON THE SPOTIFY - Gina - Sundari; Veny Purba (Pusat Penelitian dan Pengembangan Aplikasi Informatika, Informasi dan Komunikasi Publik (APTIKA dan IKP) Badan Penelitian dan Pengembangan SDM Kementerian Komunikasi dan Informatika, 2020)
Podcasts are now developing and much averred by millennials. The ease in producing podcasts makes people participate in making podcasts, so anyone can become a podcaster. The most widely used digital platform to listen to podcasts today is the Spotify platform. The purpose of this research is to find out how the communication strategy used by podcaster’s in creating podcast content on the Spotify digital platform. This research uses a qualitative approach with a case study method, and data collected from in-depth interviews and observations. The case study was conducted on the Podcast Awal Minggu. The analytical theory used in this study of Harold D. Laswell's communication theory and new media's theory. The results of this study are communication strategies used by the podcaster’s Awal Minggu : (1) consistent (2) conducting promotions using social media assets that are owned by the right hat and topic or can be called social climbing (3) collaboration is also carried out so that get followers. Collaboration is an important element for stealing followers.